Evaluating the efficacy of a priming dose of cyclophosphamide prior to pembrolizumab to treat metastatic triple negative breast cancer - Karen McKinnon; Kristen Cowens; Dante Bortone; Lisa Carey; Trevor Jolly; Hyman Muss; Katherine Reeder-Hayes; Rebecca Kaltman; Rachel Jankowitz; Vinay Gudena; Oludamilola Olajide; Charles Perou; et al. (Journal for ImmunoTherapy of Cancer)
Purpose Triple negative breast cancer (TNBC) is characterized by the presence of immune cells in the tumor microenvironment, however, the response to single-agent immune checkpoint inhibitor (ICI) therapy is modest. Preclinical models have demonstrated that intratumoral regulatory T cells (Tregs) dampen the antitumor response to ICI. We performed a single-arm phase II trial to evaluate the efficacy of a single low dose of cyclophosphamide (Cy) to deplete Tregs administered before initiating pembrolizumab.Patients and methods 40 patients with pretreated metastatic TNBC were enrolled. The primary endpoints were progression-free survival (PFS) and change in peripheral blood Tregs after Cy. Secondary endpoints included overall response rate (ORR), duration of response, overall survival, treatment-related adverse events (AEs), and correlative evaluations.Results Median PFS was 1.8 months, and the ORR was 21%. Tregs were not significantly decreased after Cy prior to ICI (−3.3%, p=0.19), and increased significantly after the first cycle of therapy (+21% between cycles 1 and 2, p=0.005). Immune-related AEs were similar to historical pembrolizumab monotherapy, and were associated with response to therapy (p=0.02). Patients with pretreatment tumors harboring increased expression of B cell metagene signatures and increased circulating B cell receptor repertoire diversity were associated with clinical response and immune-related toxicity (IRT).Conclusions Among patients with heavily pretreated TNBC, Cy prior to pembrolizumab did not significantly deplete Tregs, and in those with decreased numbers there was rapid recovery following therapy. Increased B cell gene expression in baseline samples was associated with clinical response and IRT.